Administration of Moringa (Moringa oleifera) Fruit Seed Extract Cream 6% Prevented Collagen Depletion in Ultraviolet B-Induced Guinea Pigs (Cavia Porcelus) Skin - Yuziana Yuziana; Wimpie Pangkahila; Anak Agung Gede Putra Wiraguna (Fakultas Kedokteran Universitas Udayana, 2021)
ABSTRACT Background: Skin is often exposed to the environment such as Ultraviolet (UV) radiation which causes skin aging or photoaging. UVB-induced photoaging is characterized by a decrease in the amount of collagen. Natural ingredients that contain antioxidants, such as Moringa fruit seed extract containing bioactive compounds, are expected to prevent a decrease in the amount of collagen that eventually slows skin aging. The purpose of this study was to prove that administration of Moringa (Moringa oleifera) fruit seed extract cream 6% prevents collagen depletion in ultraviolet B-induced guinea pigs (Cavia porcelus) skin. Methods: This study was an experimental study with post-test only control group design. The subjects used in this study were 36 guinea pig (Cavia porcelus), 3 months old, male, and weighing 300-350 gr. The guinea pigs were grouped randomly into 2 groups with 18 guinea pigs/group. The first group (control) was the group treated with basic cream and exposed to UVB rays of 840 mJ/cm2; while the second group (treatment group) was treated with Moringa fruit seed extract cream 6% and exposed to UVB rays of 840 mJ/cm2. After 28 days of treatment, the guinea pigs were euthanized and histopathological examination of collagen was carried out with Sirius red staining. Results: The results showed that the average amount of collagen in the control group was 59.73 ± 2.31%. In the group of Moringa fruit seed extract cream 6%, the collagen amount was 84.07 ± 2.03%. Significance analysis using independent t-test showed a p value of <0.001 which means that there was a difference in the average amount of collagen between groups. Conclusion: In this study, the results indicated that administration of Moringa (Moringa oleifera) fruit seed extract cream 6% prevented collagen depletion in ultraviolet B-induced guinea pigs (Cavia porcelus) skin. Keywords: Moringa fruit seeds, collagen, guinea pigs, ultraviolet B.